DEMOGRAPHIC DATA OF THE OUTPATIENTS ABOVE 65 YEARS OLD ABOUT OSTEOPOROSIS AND THE RISK FACTORS IN ATATÜRK BALNEOTHERAPY AND REHABILITATION CENTER - Alev Ay; Zeynep Sağırkaya; Merih Yurtkuran (Archives of Rheumatology, 2005)
The aim of this retrospective study is to determine the rates of osteoporosis and fractures in men and women older than 65 years and to see the correlations between demographic and densitometric data. 208 outpatients (men and women) above the age of 65 years were examined and interrogated by a questionnaire about demographic characteristics of age, sex, education, preexisting diseases, nutrition habits, physical activity level, fracture story and medical therapy effecting calcium metabolism. Thoracolumbar and pelvis X-rays and T scores of BMD (Bone Minoral Density) by Dual Energy Xray Absorptiometry (DEXA) were evaluated. Education level of the male population was higher and the BMIs were lower than the females. Peripheric Fracture (PF) rate was 7% and compression fracture (CF) rate was 13%. There was positive correlation between PF and CF, tea drinking habbit and femur BMD and also T scores of spine BMD and femur BMD in men. CF and femur BMD T scores, physical activity level and VAS of the dorsolumbar region and physical activity level and CVS disfunction were were negatively correlated in women. Tea drinking habbit and femur BMD T scores were positively, physical activity level and CVS disfunction were negatively correlated in men. In conclusion, physical activity level, preexisting fracture, tea drinking habbit and femur BMD have effects on the outcome of the fractures and pain which are the components of osteoporosis.